2020
DOI: 10.21203/rs.3.rs-46831/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network Pharmacology-based Strategy for Studying the Mechanism of Gegen Qinlian Decoction for the Treatment of Acute Colitis

Abstract: Background: Gegen Qinlian Decoction(GQD) has been used to treat acute colitis (AC) for several years in China and it has shown good efficacy. However, the active components and target proteins of its anti-AC effects remains to be deciphered. Methods: In this study, serum pharmacochemistry and network pharmacology strategy were integrated to identify the constituents in blood and the mechanism of GQD for the treatment of AC. Ultra-performance liquid chromatography and LTQ-Orbitrap mass spectrometry(UPLC-LTQ-Orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a study by Zhang Jiacheng, it was found that the minimum amount of water added for GQD decoction was nine times the amount of the drug mass, and the time of decoction was 50 min; otherwise, it affected the precipitation of the active ingredients of the drug, thus affecting the efficacy (20). Its key constituent flavonoids, alkaloids, and saponins were identified through ultra-high-performance liquid chromatography and mass spectrometry (21). It has the effect of clearing the liver, diarrhea, heat, and intestines, and can be applied to diseases such as acute gastroenteritis, ulcerative colitis, gastroparesis, colon cancer, diabetes mellitus with lower limb vasculopathy, and peripheral neuropathy (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Zhang Jiacheng, it was found that the minimum amount of water added for GQD decoction was nine times the amount of the drug mass, and the time of decoction was 50 min; otherwise, it affected the precipitation of the active ingredients of the drug, thus affecting the efficacy (20). Its key constituent flavonoids, alkaloids, and saponins were identified through ultra-high-performance liquid chromatography and mass spectrometry (21). It has the effect of clearing the liver, diarrhea, heat, and intestines, and can be applied to diseases such as acute gastroenteritis, ulcerative colitis, gastroparesis, colon cancer, diabetes mellitus with lower limb vasculopathy, and peripheral neuropathy (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%